Epidemiological Characteristics of Pediatric Supracondylar Humerus Fractures at Tobruk Medical Center (2020–2024) (The International Journal for Scientific Research, 2025)
Background and Rationale: Supracondylar humerus fractures are the most common type of elbow fracture in children and represent a significant proportion of pediatric orthopedic injuries. These fractures often result from falls on an outstretched hand and are most frequently seen in children aged 4–10 years. Early identification of demographic and seasonal trends can aid in prevention strategies and healthcare planning. Despite the high incidence of these fractures worldwide, there is limited local data from Tobruk and Eastern Libya. This study aims to fill that gap by analyzing retrospective data over a 5-year period. Methods: This retrospective descriptive study included children aged 0–15 years with radiologically confirmed supracondylar humerus fractures. Demographic data, Fracture laterality, mechanism of injury, seasonal variation, management, and outcomes were collected from medical records. Data were analyzed using SPSS version 23; categorical variables were presented as frequencies and percentages, and continuous variables as mean ± SD or median (range). Statistical significance was set at p < 0.05. Results: Eighty-nine children were included (56.2% males, 43.8% females) with a mean age of 4.97±2.57 years. Fractures were more common on the left side (57.3%). Most fractures were managed with closed reduction (96.6%), and the mean time from injury to surgery was 2.2 ± 2.4 days. Seasonal analysis showed highest incidence in autumn (30.3%) and summer (27%). Males were significantly older than females at the time of injury (5.5±2.8 vs 4.3±2.0 years, p = 0.043). No significant gender differences were observed in fracture laterality. Conclusion: Pediatric supracondylar humerus fractures in Tobruk predominantly affect children under ten years, with male predominance and left-side involvement. Closed reduction is the mainstay of treatment. Peaks in incidence occur during summer and autumn, emphasizing the need for preventive strategies and timely access to care. These findings provide baseline epidemiological data to inform local healthcare planning and future multicenter studies in Libya.
Keywords: Pediatric Fractures; Supracondylar Humerus Fracture; Epidemiology; Seasonal Variation; Libya; Tobruk Medical Center